Assessment of primary health care: health professionals’ perspective - Silva, Simone Albino da; Nogueira, Denismar Alves; Paraizo, Camila Maria da Silva; Fracolli, Lislaine Aparecida (Revista da Escola de Enfermagem da USP, 2014)
Objective To assess primary health care attributes of access to a first contact, comprehensiveness, coordination, continuity, family guidance and community orientation. Method An evaluative, quantitative and cross-sectional study with 35 professional teams in the Family Health Program of the Alfenas region, Minas Gerais, Brazil. Data collection was done with the Primary Care Assessment Tool - Brazil, professional version. Results Results revealed a low percentage of medical experts among the participants who evaluated the attributes with high scores, with the exception of access to a first contact. Data analysis revealed needs for improvement: hours of service; forms of communication between clients and healthcare services and between clients and professionals; the mechanism of counter-referral. Conclusion It was concluded that there is a mismatch between the provision of services and the needs of the population, which compromises the quality of primary health care.